Metabolic profile of obese and non-obese patients with Polycystic Ovary Syndrome (Research, Society and Development, 2021)
To evaluate the clinical and metabolic characteristics of women with Polycystic Ovary Syndrome (PCOS) of different phenotypes. Controlled and analytical cross-sectional design. Sampling was non-probabilistic and composed of 120 participants, forming four groups: 1A (without PCOS and normal weight); 1B (without PCOS and with abnormal weight); 2A (PCOS and normal weight) and 2B (PCOS and abnormal weight). Structured form and electronic medical record were used for data collection. Uni and bivariate statistics were performed using IBM® SPSS® 21.0 software. Metabolic syndrome predominated in groups 2A (7.1%) and 2B (37.5%) compared to the respective controls 1A (0%) and 1B (19.2%). Similarly, the insulin was higher in groups 2A (15.7±8.2) and 2B (19.8±6.7) compared to 1A (6.5±4) and 1B (6.5±4,8). The 2-hour oral glucose tolerance test (OGTT) was superior in group 2B (132.1±31.3) compared to group 1B (115.2±20.8) and in group 2A (111.9±24.7) in relation to 1A (105.4±12.1). Total and free testosterone levels were higher in groups 2A (4.4±6.7 and 1.4±1.5, respectively) and 2B (2±2.4 and 1±0.9) in relation to 1A (1,2±3.8 and 0.2±0.3) and 1B (0.5±0.4 and 0.2±0.4). The systolic blood pressure was higher in 2B (125.8±11.7) than 1B (123.3±11.7) and in 2A (122.1±10) compared to 1A (113.7±8,7). PCOS is associated with an unfavorable metabolic profile, with significance for insulin resistance, hyperandrogenism and metabolic syndrome, making essential the broad and multidisciplinary clinical follow-up.